Relative golf performance between men and women: A comparison of absolute differences in performance between players on the PGA and LPGA tours considering physiological and anthropometric sex-based differences - Jemina Villanen; Arve Vorland Pedersen (PLoS ONE, 2026)
Golf is an increasingly popular sport and presents fierce competition at the professional level. The Professional Golfers’ Association (PGA) Tour is the most prestigious professional men’s tour in golf, whereas the Ladies Professional Golf Association (LPGA) Tour is the equivalent for women. Among professionals, although women golfers play shorter courses than men, the rules and regulations for men and women are similar. In turn, differing requirements due to anthropometric and physiological sex-based differences may affect variables such as choice of club and playing strategy. Therefore, in our study, we aimed to identify differences in golf performance between men and women and to discuss whether the differences correspond with known physiological and anthropometric sex-based differences. We conducted a natural experiment, using publicly available data, comparing world class men and women golfers’ performances on their respective tours. Performance and course data were collected on all 50 PGA and 32 LPGA Tournaments in the 2021–2022 season and differences between the tours were identified. The lengths of the courses and holes on the LPGA Tour were approximately 90% of those on the PGA Tour. Overall, women had better driving accuracy than men but scored fewer eagles and rounds in the 60s. Anthropometric and physiological differences likely contribute to women’s adapted movement strategies during the swing and cause them to choose playing strategies that men do not, primarily in driving and approach shots. Altogether, our results suggest that women’s golf courses are likely not sufficiently scaled according to anthropometry or physiology. Thus, golf remains more demanding for women, which may, at least partly, explain their differences in performance compared with men.